ENERGY SUPPORT FOR THE PERMANENT MISSION TO MARS - Kulyk, Mykola; Volianska, Larysa; Kirchu, Fedor (Proceedings of National Aviation University (archive), 2020)
The concept of using a closed-cycle gas turbine plantfor a planetary energy supply system is considered in the article. The analysis of the currently relevant projects in the field of creating closed-cycle gas turbine plants for energy supply of spacecraft and autonomous objects is given. General information on the main subsystems of power plants operating according Brayton closed cycle is presented. It is shown that the closed-cycle gas turbine having a compact and simple construction demonstrates to be an optimum approach for space nuclear power. The constituent components of the plant performing the cycle processes are a compressor, a turbine, a heat source, a cold source and a regenerator. Therefore, the working fluid performs a heat cycle in which thermal energy is converted into electrical energy, able to use in space and planetary devices.Particular attention is paid to the justification of the choice of the working fluid, the physicochemical properties of which significantly affect the working process of the plant and determine its main characteristics. The thermodynamic calculation of one of such plant is presented.